Innovation, creative destruction, and price theory - Bloch, Harry; Metcalfe, S. (Oxford University Press, 2018)
Our purpose in this paper is to consider developments in price theory required to facilitate the evolutionary analysis of economic change. Evolution is always a matter of change and, although its driving force is innovation, the price mechanism is central to how innovations are resolved into economic development. That is Schumpeter's great theme, but he said relatively little about who sets prices or how and why prices are changed. We focus particularly on price determination in markets disrupted by innovations, where firms are necessarily heterogeneous. We contrast the evolutionary paths followed by prices and market structure when prices are determined by market clearing to the paths when prices are determined through the application by firms of administered rules and routines to achieve their strategic objectives. This links the analysis to theories of administered prices and post- Keynesian price theories more broadly. Interaction of innovators with their customers and with established competitors create the context for the evolution of pricing rules along with differential firm growth, which together generates structural change in the industry and the economy. We show that analyzing how the introduction and diffusion of innovations impact on the rules and routines provides the foundation for a broadly applicable evolutionary price theory.